PHYSICAL THERAPY INTERVENTIONS IN CHILDREN WITH CANCER - Fatma Betül Çakır (Sabiad)
Children with cancer experience severe adverse effects from cancer or as a sequela of cancer treatment. These side effects can affect major body systems such as musculoskeletal, cardiovascular and neurological systems and impact participation in daily living activities and thus quality of life. These sequelae are to be lessened with physical therapy, rehabilitation, or neuropsychological treatment according to the requirements of the patients. Thus, awareness of the rehabilitation needs of children with cancer is crucial to enhance a healthy life with quality. Recommendations concerning the quality of life among adults are included in the guidelines, but data including recommendations for children are limited.